Edge‐Decorated Polycyclic Aromatic Hydrocarbons by an Oxidative Coupling Approach. Issue 10 (29th December 2022) - Gilmartin, Philip; Vu, Cassandra; Rotella, Madeline; Kaur, Jasjit; Kozlowski, Marisa
Abstract: Oxidative phenol coupling reduces reliance on halo/metalated substrates used in conventional redox neutral couplings. A new strategy for constructing polycyclic aromatic hydrocarbons (PAHs) that incorporates oxidative phenol coupling is outlined in a three‐stage approach: oxidative fragment coupling, linking of the two resultant units, and oxidative cyclization. The protocol allows rapid assembly of both planar and helical systems with a high degree of edge functionalization. The incorporation of 12 alkoxy groups on systems with 12 rings gave rise to lower optical gaps compared to systems with a lesser degree of edge functionalization. Abstract : Alkoxy highly edge‐decorated polycylic aromatic hydrocarbons (PAHs) have been formed. Oxidative cross coupling of phenols constructs frameworks without any need for the prefunctionalization required by conventional methods. Moreover, smaller optical gaps can be achieved relative to systems of similar size.